Prostate Cancer Screening and Willingness among Staff of Faculties of Health Sciences and Technology and Basic Medical Sciences, University of Nigeria Nsukka, Enugu State, Nigeria - Rita I. Ogu; Cornelius O. Ogu; Christopher C. Wogu (International Journal of Medicine and Health Development)
Background: Previous studies reported good awareness and knowledge but poor uptake of prostate cancer screening across various settings and countries. Additionally, previous studies reported positive willingness for prostate cancer screening based on questionnaire responses. Objective: The present study adopted an “active physical method” to study the willingness for prostate cancer screening among staff of two faculties in a College of Medicine in southeastern Nigeria. Materials and Methods: This cross-sectional study recruited 66 participants out of 80 male staff in the two faculties. A structured questionnaire was used to obtain socio-demographic data, willingness, and uptake history from male staff aged 36 years and above. Blood samples were collected immediately into lithium heparin tubes from those who declared willingness for prostate cancer screening. The blood samples were used for total prostate-specific antigen (PSA) assay. The assay was conducted in two steps. First, all the samples were subjected to a semi-qualitative assay using a rapid test kit. Second, the samples that reacted positively with the rapid test kit were subjected to the second quantitative assay for PSA, along with control samples selected from the negative results. Results: The results showed that the willingness was 57/66 (86.4%). The prevalence of positive results (PSA >4ng/mL) from the screening was 9/57 (15.8%) for both techniques combined. Additionally, 5/57 (8.8%) were found to be positive for both techniques. Conclusions: There is a high willingness for “active prostate cancer screening” among the the staff of the institution. The prevalence of positive results was slightly high. We recommend the implementation of effective prostate cancer screening programs in Nigeria.